Inheritance of time to flowering in cowpea (Vigna unguiculata (L.) Walp.) - Ishiyaku, M.; Singh, B.; Craufurd, Peter Q. (Springer, 2005)
Time to flowering and maturity is an important adaptive feature in annual crops, including cowpeas (Vigna unguiculata (L.) Walp.). In West and Central Africa, photoperiod is the most important environmental variable affecting time to flowering in cowpea. The inheritance of time from sowing to flowering (f) in cowpeas was studied by crossing a photoperiod-sensitive genotype Kanannnado to a photoperiod-insensitive variety IT97D-941-1. Sufficient seed of F1, F2, F3 and backcross populations were generated. The parental, F1, F2, F3 and the backcross populations were screened for f under long natural days (mean daylength 13.4 h per day) in the field and the parents, F1, F2 and backcross populations under short day (10 h per day) conditions. The result of the screening showed that photoperiod in the field was long enough to delay flowering of photoperiod-sensitive genotypes. Photoperiod-sensitivity was found to be partially dominant to insensitivity. Frequency distribution of the trait in the various populations indicated quantitative inheritance. Additive (d) and additive × dominance (j) interactions were the most important gene actions conditioning time to flowering. A narrow sense heritability of 86% was estimated for this trait. This will result in 26 days gain in time to flowering with 5% selection intensity from the F2 to F3 generation. At least seven major gene pairs, with an average delay of 6 days each, were estimated to control time to flowering in this cross.